Citrinin Determination in Red Fermented Rice Products by Optimized Extraction Method Coupled to Liquid Chromatography Tandem Mass Spectrometry (LC‐MS/MS). Issue 6 (5th May 2015) - Ji, Xiaofeng; Xu, Junfeng; Wang, Xiaofu; Qi, Peipei; Wei, Wei; Chen, Xiaoyun; Li, Rui; Zhou, Yu
Abstract A rapid and sensitive method was developed and validated for citrinin determination in red fermented rice products by liquid chromatography tandem mass spectrometry (LC‐MS/MS) under the selected reaction monitoring mode. Sample preparation was especially focused, and the quantitative methods of LC‐MS/MS and high‐performance liquid chromatography with fluorescence detection (HPLC‐FLD) were compared. In red fermented rice samples, the limit of detection was 1.0 μg/kg for LC‐MS/MS compared to 250 μg/kg for HPLC‐FLD, the limit of quantification was 3.0 μg/kg for LC‐MS/MS compared to 825 μg/kg for HPLC‐FLD. High correlation coefficient was obtained (R2 = 0.999) within the linear range (0.1 to 100 μg/L) in the MS method. The recoveries ranging from 80.9% to 106.5% were obtained in different spiking concentrations. The average intra‐ and inter‐day accuracy ranged from 75.4% to 103.1%, and the intra‐ and inter‐day precisions were from 3.3% to 7.9%. The developed method was applied to 12 commercial red fermented rice products, and citrinin was found in 10 samples ranging from 0.14 to 44.24 mg/kg. Compared to traditional qualitative and quantitative methods, the newly developed LC‐MS/MS method for citrinin determination includes the merits of using a small amount of extraction solvent, simple preparation steps, and high sensitivity.